Clinical application of a gadolinium‐based capsule as an MRI contrast agent in slow transit constipation diagnostics. Issue 6 (1st February 2017) - Zhi, M.; Zhou, Z.; Chen, H.; Xiong, F.; Huang, J.; He, H.; Zhang, M.; Su, M.; Gao, X.; Hu, P.
Abstract: Background: As a traditional method for the assessment of colon dynamics, radio‐opaque markers (ROMs) are limited in clinical use because of their ionizing radiation. We compared the accuracy and applicability of gadolinium‐based capsules with ROMs in the measurement of colon dynamics in healthy controls and slow transit constipation (STC) patients. Methods: Seven patients with STC and nine healthy controls under a normal diet orally consumed ROMs and gadolinium‐based capsules simultaneously. All subjects underwent X‐ray and magnetic resonance imaging (MRI). Healthy control images were acquired at 12, 24, and 48 h, and STC patient images were acquired at 24, 48, and 72 h. The scores based on the position of the labeling capsules and ROMs in the colon and the colon transit times (CTTs) in the two groups were compared. Key Results: The CTTs obtained via the ROMs were 34.7±17.4 and 67.3±6.5 h in the healthy controls and STC patients, respectively ( P <.05). The CTTs obtained via MRI were 30.9±15.9 and 74.1±7.2 h in the healthy controls and STC patients, respectively ( P <.05). The CTTs of the STC patients were significantly longer than the healthy controls. The correlation ( r s ) between the scores based on the position of the labeling capsule and ROMs in the healthy group and the STC patients was .880 ( P <.05) and .889 ( P <.05), respectively. Conclusions and Inferences: As a MRI contrast label, gadolinium‐based capsules exhibit results comparable to ROMs in colon motility measurements. Abstract : As a traditional method for the assessment of colon dynamics, radio‐opaque markers (ROMs) are limited in clinical use because of their ionizing radiation. We compared the accuracy and applicability of gadolinium‐based capsules with ROMs in the measurement of colon dynamics in healthy controls and slow transit constipation (STC) patients. The assessment results of gadolinium‐based capsules were in consonance with ROMs. As a MRI contrast label, gadolinium‐based capsules exhibit results comparable to ROMs in colon motility measurements.